BANKING COMPANY EFFICIENCY IN THE DIGITAL TRANSFORMATION ERA: A MAXDEA APPLICATION BASED INTERMEDIATION APPROACH - Dwijayantie, Rinti (BALANCE: JOURNAL OF ISLAMIC ACCOUNTING, 2025)
This study aims to measure the operational efficiency of the banking industry in Indonesia during the era of digital transformation using the Data Envelopment Analysis (DEA) method with an intermediation approach and uses MaxDEA Software version 8. The research sample consists of 27 banks listed on the Indonesia Stock Exchange during the 2021–2023 period. The input variables include operating costs, number of employees, and third-party funds, while the output variables consist of total loans and net income. The analysis results indicate an upward trend in average efficiency, from 0.67 in 2021 to 0.79 in 2023. However, efficiency levels across banks exhibit significant disparities. PT Allo Bank Indonesia Tbk (BBHI) is recorded as the only bank that achieved perfect efficiency for three consecutive years, while several other banks show substantial potential for improvement, particularly in terms of increasing loans and net income. The potential improvement analysis reveals that banks with low efficiency require major restructuring, whereas those with high efficiency only need minor adjustments. This study also highlights the crucial role of digital transformation in enhancing efficiency, particularly through the adoption of digital banking technologies, process automation, and the use of big data. These findings provide strategic implications for bank management and regulators in formulating sustainable efficiency improvement policies.